(untitled) (Research, Society and Development, 2019)
The objective of this study is to collect information about the feelings that have been reported in published articles about the impacts of mastectomy on women diagnosed with breast cancer in relation to self - image. This is an integrative review of the literature based on the Electronic Electronic Library Online (SciELO) electronic database, using the Health Sciences Descriptors (DECS): Autoimaging / Mastectomy, Sexuality / Mastectomy and Mastectomy, interconnected by Boolean operators AND and OR published in the period from 2010 to 2017. There were 179 studies, of which six met the objective. The application of this method resulted in six subjects that were most present in the samples studied. They are: alopecia, sexuality, breast loss, scarring, shame and fear of finitude of life. The process of mastectomy causes the woman to physical and psychological changes. In this sense it is fundamental that the nurse professional understands the woman as a whole, improving and providing information about sexuality and self-image, as well as about the disease.